Access to general practice during the COVID-19 pandemic - a cross-sectional view of the opinions of adults who use social media - Gabriela Mineva; Aoibhin McCool; Bethany Rogers; Monika Volz; Dana Pearl; Irene Kiroplis; Yasmine Abo Halima; Patrick O’Donnell; Peter Hayes (James Cook University, 2023)
Introduction: The COVID-19 pandemic has had a significant impact on the health and wellbeing of people worldwide. General practices were forced to adapt to constantly changing circumstances, leading to predominance of virtual consultations. The aim of this study was to examine the impact the pandemic had on the ability of patients to access general practice. Other focuses included determining the nature of changes to appointment cancellations or delays and the level of disruption to long-term medication regimes during this period.Methods: A 25-question online survey was administered using Qualtrics®. Adult patients of Irish general practices were recruited via social media between October 2020 and February 2021. The data were examined for associations between participant groupings and key findings using chi-squared tests.Results: 670 persons participated. Half of all doctor-patient consultations during that time were completed virtually, predominantly via telephone. Overall, 497 (78%) participants accessed their healthcare teams as scheduled, and without disruption. 18% of participants (n=104) reported difficulty in accessing their long-term medications; those who were younger, and those who typically attend general practice on a quarterly or more basis, were associated most with this disruption (p<0.05; p<0.05).Discussion: Despite the COVID-19 pandemic, Irish general practice has maintained its schedule for appointments in greater than three quarters of cases. There was a clear shift away from face-to-face consultations to telephone appointments. Maintaining the prescription of long-term medications for patients remains a challenge. Further work needs to be done to ensure the continuation of care and undisrupted medication schedules during any future pandemics.